Follow-Up Care Adherence After Hospital Discharge in Children With Traumatic Brain Injury. Issue 3 (May 2018) - Spaw, Alexandra J.; Lundine, Jennifer P.; Johnson, Sarah A.; Peng, Jin; Wheeler, Krista K.; Shi, Junxin; Yang, Ginger; Haley, Kathy J.; Groner, Jonathan I.; Xiang, Henry
Abstract : Objective: To investigate factors associated with follow-up care adherence in children hospitalized because of traumatic brain injury (TBI). Design: An urban level 1 children's hospital trauma registry was queried to identify patients (2-18 years) hospitalized with a TBI in 2013 to 2014. Chart reviewers assessed discharge summaries and follow-up instructions in 4 departments. Main Measures: Three levels of adherence—nonadherence, partial adherence, and full adherence—and their associations with care delivery, patient, and injury factors. Results: In our population, 80% were instructed to follow up within the hospital network. These children were older and had more severe TBIs than those without follow-up instructions and those referred to outside providers. Of the 352 eligible patients, 19.9% were nonadherent, 27.3% were partially adherent, and 52.8% were fully adherent. Those recommended to follow up with more than 1 department had higher odds of partial adherence over nonadherence (adjusted odds ratio [AOR] = 5.8, 95% CI: 1.9-17.9); however, these patients were less likely to be fully adherent (AOR = 0.1; 95% CI: 0.1-0.3). Privately insured patients had a higher AOR of full adherence. Conclusions: Nearly 20% of children hospitalized for TBI never returned for outpatient follow-up and 27% missed appointments. Care providers need to educate families, coordinate service provision, and promote long-term monitoring.